A representação da mulher e as questões de gênero na toponímia urbana de Caicó-RN - Araújo, Claudia Medeiros de (2013)
This piece wants to investigate the relations between gender identities and the toponymy in Caicó city. To do so, we will discuss the reason why places are named, the practice of naming places, so as the process of choosing the names of neighborhoods, streets and city public squares. Thereby, we will investigate the space changes in Caicó city since its formation, as a village, until the decade of 1970. This period of time was chosen in order to discuss the toponymic process of the city, besides having noticed that public places and locations in Caico with the feminine nominations only appear from the second half of the 60s decade and in the beginning of the 70s. This way, we preferred to investigate who were the first Caicó women to have their names in the urban space; why women only begin to have homage from the decade of the 60s on; what is the importance and the location of the places with feminine names; and what gender image is there on this homage